2(t-4)+6t=4(2t+3)-9

Simple and best practice solution for 2(t-4)+6t=4(2t+3)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(t-4)+6t=4(2t+3)-9 equation:


Simplifying
2(t + -4) + 6t = 4(2t + 3) + -9

Reorder the terms:
2(-4 + t) + 6t = 4(2t + 3) + -9
(-4 * 2 + t * 2) + 6t = 4(2t + 3) + -9
(-8 + 2t) + 6t = 4(2t + 3) + -9

Combine like terms: 2t + 6t = 8t
-8 + 8t = 4(2t + 3) + -9

Reorder the terms:
-8 + 8t = 4(3 + 2t) + -9
-8 + 8t = (3 * 4 + 2t * 4) + -9
-8 + 8t = (12 + 8t) + -9

Reorder the terms:
-8 + 8t = 12 + -9 + 8t

Combine like terms: 12 + -9 = 3
-8 + 8t = 3 + 8t

Add '-8t' to each side of the equation.
-8 + 8t + -8t = 3 + 8t + -8t

Combine like terms: 8t + -8t = 0
-8 + 0 = 3 + 8t + -8t
-8 = 3 + 8t + -8t

Combine like terms: 8t + -8t = 0
-8 = 3 + 0
-8 = 3

Solving
-8 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x-3+73=90 | | 4s-10=8-2s | | X-24=53 | | 4ln(5x+4)=22 | | g(3y)x-2x^2= | | 3(2c+1)=2(4c-1) | | 7n=219 | | 15d=3d | | (m-1)x^2-2mx-m-4=0 | | 15=9x-1 | | 7(6)+4+7(6)+4-4+(7(6)+4)=180 | | 1500mL=L | | f(2x-1)=8x^2-2x | | 360*17/24 | | 5.5+7= | | X-0.2=100 | | 3m-1=2m-6 | | 30=10+.75x | | 4x^4+184x=10 | | 10x+20*47-20x=640 | | 8+2(4w-3)=-2(7w-5)+6w | | 10n-7=-13 | | 8x-1=89 | | 10(7.5)=2(7.5)+60 | | 19x-5=11x-45 | | 5x=6-4x^2 | | x-5+x=2x-4 | | 2x+x+5=68 | | 7(6)+4+7(6)+4-4+(7(6)+4)2=180 | | 6x+3=4a-1 | | 2n-6=4n+24 | | 2(x-4)+x=-9(5-x) |

Equations solver categories